Message in a Bottle: Dialog between Intestine and Skin Modulated by Probiotics - Friedrich, Adrián David (2017)
At the beginning, probiotics were used exclusively for gastrointestinal conditions. However, over the years, evidence has shown that probiotics exert systemic effects. In this review article, we will summarize recent reports that postulate probiotic treatment as an efficient one against skin pathologies, such as cancer, allergy, photoaging and skin infections. The focus will be restricted to oral probiotics that could potentially counteract the ultraviolet irradiation-induced skin alterations. Moreover, the possible underlying mechanisms by which probiotics can impact on the gut and exert their skin effects will be reviewed. Furthermore, how the local and systemic immune system is involved in the intestine-cutaneous crosstalk will be analyzed. In conclusion, this article will be divided into three core ideas: (a) probiotics regulate gut homeostasis; (b) gut and skin homeostasis are connected; (c) probiotics are a potentially effective treatment against skin conditions.